Financial development during COVID-19 pandemic: The role of coronavirus testing and functional labs - Muhammad Khalid Anser; Muhammad Azhar Khan; Khalid Zaman; Abdelmohsen A. Nassani; Sameh E. Askar; Qazi Muhammad Moinuddin Abro; Ahmad Kabbani (Financial Innovation, 2021)
The outbreak of the SARS-CoV-2 virus in early 2020, known as COVID-19, spread to more than 200 countries and negatively affected the global economic output. Financial activities were primarily depressed, and investors were reluctant to start new financial investments while ongoing projects further declined due to the global lockdown to curb the disease. This study analyzes the money supply reaction to the COVID-19 pandemic using a cross-sectional panel of 115 countries. The study used robust least square regression and innovation accounting techniques to get sound parameter estimates. The results show that COVID-19 infected cases are the main contributing factor that obstructs financial activities and decrease money supply. In contrast, an increasing number of recovered cases and COVID-19 testing capabilities gave investors confidence to increase stock trade across countries. The overall forecast trend shows that COVID-19 infected cases and recovered cases followed the U-shaped trend, while COVID-19 critical cases and reported deaths showed a decreasing trend. Finally, the money supply and testing capacity show a positive trend over a period. The study concludes that financial development can be expanded by increasing the testing capacity and functional labs to identify suspected coronavirus cases globally.
Keywords: 650; COVID-19 pandemic; Financial development; Infected cases; Innovation accounting matrix; Robust least square estimator; Testing capacity